A case report of a lung abscess as a rare complication of a pyogenic liver abscess. Issue 48 (3rd December 2021) - Kim, Hee Yeon; Lee, Hyo-Jin
Abstract: Rationale: A hepatobronchial fistula and lung abscess following a pyogenic liver abscess is a rare entity and it is not easy to diagnose this condition based on the symptoms and chest radiography. Patient concerns: An 81-year-old man presented with productive cough and dyspnea. Diagnosis: Chest radiography indicated increased opacities in the right lower lung field with an air-fluid level suggestive of pneumonia complicated by a lung abscess. Chest and abdominal computed tomography revealed an abscess in the right lower lung field that bordered an abscess at segment 7 of the liver. Tubography confirmed a fistula between the liver and lung abscesses. Interventions: Due to communication between 2 abscesses, transhepatic approach was done instead of transpleural approach to avoid complications. Outcomes: A liver abscess complicated by a lung abscess was resolved following percutaneous transhepatic drainage of the liver abscess and antibiotic administration. Lessons: Though uncommon, the lack of suspicion of sub-diaphragmatic liver abscess often lead to a delay in diagnosis and proper treatment. Our case implies the importance of computed tomography in early diagnosis of liver abscess in case of lung abscess in the right lower lung field.